Kerentanan Sistem Pertanian akibat Eksternalitas Industri Energi: Studi Kasus Proyek Geothermal di Desa Batukuwung Padarincang, Banten (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2025)
The Geothermal Power Plant (PLTP) project in Batukuwung Village, Padarincang District, Serang Regency, has raised concerns among the community about the threat of environmental damage and the disruption of the sustainability of local agricultural systems. During this time, the community relies on traditional agriculture that is closely tied to local social, cultural and ecological values. This research aims to assess the social and ecological impacts of the PLTP project on the lives of village communities. The method used is a descriptive qualitative approach with a case study, through purposive sampling techniques for in-depth interviews with affected residents, as well as online media analysis. The results show that the presence of the project has created ecological and social vulnerabilities, especially disruptions to water and land access, and narrowed the space for community participation in decision-making. The findings show that the clean energy narrative is not always in line with the reality on the ground. This research emphasizes the importance of the principles of ecological justice and local community sovereignty in energy development policies, especially in areas that depend on natural sustainability.